Fish : Joanna Farrow - Farrow, Joanna (London, United Kingdom : New Holland Publishers, 2012)
All you need to know about the main ingredient that is seafood. This book is designed for the novice and the experienced cook who enjoys the ocean tastes of seafood. There's really no mystery to cooking delicious fish.
Sustainable fishing 10 -- Buying fish 12 -- Storing fish 15 -- Preparation techniques 16 -- Baking and roasting 30 -- Grilling and barbecuing 62 -- Frying 92 -- Stewing, braising and poaching -- Steaming and microwaving -- Raw, cured and smoked -- Basic recipes.
Includes index.
Keywords: COOKING -- FISH